Toxicity assessment of di(2-ethylhexyl) phthalate using zebrafish embryos: Cardiotoxic potential - Azza Naïja (19137067) (2024)
Plasticizers are considered as newly emerged contaminants. They are added to plastics to increase their flexibility and softness. Phthalate plasticizers including the Di-2-ethylhexyl phthalates (DEHP) are toxic and induce adverse effects on the different organization levels of the environment. In the current study, we investigated the potential toxicity of DEHP using Zebrafish as a biological model. Five ascending concentrations of DEHP were tested in embryos throughout 96 hpf: 0.0086, 0.086, 0.86, 8.6, and 86 mg/L. Embryotoxicity assessments revealed limited lethal effects on DEHP-exposed embryos, yet notable anticipation of the hatching process was observed at 48 hpf. Although DEHP showed negligible influence on the length and pericardial area of exposed embryos, it led to multiple bodily deformities. Gene expression analyses of key cardiogenic and inflammatory genes evidenced alterations in tbx20, bcl2, and il1b expression in Zebrafish embryos at 96 h post-fertilization. Results from the cardiac function analysis displayed that DEHP significantly affected the arterial pulse and linear velocity within the Posterior Cardinal Vein (PCV) of exposed fish. These findings strongly advance that even at low concentrations, DEHP can be considered as potential toxic agent, capable of inducing cardiotoxic effects. Other Information Published in: Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cbpc.2024.109956